Orthopedic Surgery Rotation : Practical Strategies for Success for Senior Medical Students - Eltorai, Adam E. M.; Eberson, Craig P.; Daniels, Alan H. (Springer International Publishing : Imprint: Springer, 2017)
The 4th year of medical school represents an important transition with new goals and expectations. Matching into orthopedic surgery residency is increasingly competitive. Performing well on orthopedic surgery rotations during the 4th year of medical school is critical for match success. The goal of this guide book is to help students ace their orthopedic rotations. Orthopedic Surgery Rotation focuses on practical tips for success from optimal study resources, key technical skills, and strategies for being a standout orthopedic team player. Each chapter is written by current orthopedic residents, who not only know from personal experience on how to excel but also are actively involved in evaluating the performance of 4th year medical students. This book will serve as tool to propel students to the next level and help them start their journey as orthopedists on the right foot.
Keywords: Medicine.; Orthopedics.; Sports medicine.; elektronické knihy; electronic books